Study on the adsorption of Rhodamine B on MoS2/RGO composite - Phan Thi Thuy Trang; Truong Thanh Tam; Vo Vien; Nguyen Hong Lien (My University, 2020)
Study on the adsorption of Rhodamine B on MoS2/RGO composite
Keywords: Hấp phụ